(untitled) (Pain medicine, 2024)
Cardiac pain during myocardial infarction is the cause of morbidity and mortality in Ukraine in 50,000 patients. The dynamics of morbidity rates from myocardial infarction in the city of Vinnytsia over five years were studied, which increased compared of the data of 2018 to 2022. Instead, there was a trend toward a decrease in the death rate from MI from 2018 to 2022, which indicates the successful operation of medical institutions and the effective treatment of these patients.